Urine-normetanephrine, a predictor of mortality risk in patients with adrenal adenomas - Albin Kjellbom; Magnus Löndahl; Malin Danielsson; Henrik Olsen; Ola Lindgren (Scientific Reports)
Abstract Urine-metanephrines are used in the screening for pheochromocytomas in patients with adrenal incidentalomas, but their potential as markers for mortality in patients with adrenal adenomas has not been studied. A retrospective cohort study was designed to investigate if urine-metanephrines were associated with mortality in patients with adrenal adenomas. Participants where consecutively included between 2005 and 2015 at two endocrine centres in southern Sweden and followed until December 31st, 2022. The exposures were 24 h-urine (tU) metanephrine and normetanephrine analysed at inclusion. The endpoint was all-cause mortality. Outcome data were obtained from the Cause of Death Register. 879 adult (≥ 18 years) patients with an incidentally discovered adrenal adenoma were included in the study and followed for a median of 9.9 years. Median age of patients was 66.7 years, and 59.6% were women. 278 patients died during follow-up. tU-normetanephrine was associated with increased mortality, adjusted hazard ratio (HR) 1.47 (95% CI, 1.27–1.69) (HR for an increase of 100 μmol/mol creatinine). There was no significant association between tU-metanephrine and mortality, HR 0.96 (0.64–1.43). tU-normetanephrine seems to be a predictor for mortality in patients with adrenal adenomas. This widely available diagnostic test may be helpful in further risk-stratifying patients with adrenal adenomas.